2017
DOI: 10.1126/science.aao1905
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of vinylidene isomerization in its anion photoelectron spectrum

Abstract: Vinylidene-acetylene isomerization is the prototypical example of a 1,2-hydrogen shift, one of the most important classes of isomerization reactions in organic chemistry. This reaction was investigated with quantum state specificity by high-resolution photoelectron spectroscopy of the vinylidene anions HCC- and DCC- and quantum dynamics calculations. Peaks in the photoelectron spectra are considerably narrower than in previous work and reveal subtleties in the isomerization dynamics of neutral vinylidene, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 59 publications
0
85
0
1
Order By: Relevance
“…It is known that hydrogen migration can be induced by exciting a molecule in many ways, as illustrated by mass or luminescence spectra resulting from electron impact ionization 10 , X-ray absorption 11 , and ionization following ion collisions 12 . A key tool for understanding hydrogen migration dynamics, developed over the course of the past few decades is ultrafast, strong-field laser induced ionization and dissociation of small hydrocarbons, including the simplest one, acetylene 1317 , and other polyatomic molecules, such as methanol 18 , ethylene glycol 19 , and acetonitrile 20 . Ultrashort VIS/NIR laser pulses with ~10 14 W/cm 2 intensities can singly or doubly ionize molecules in the gas phase, initiating hydrogen migration.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that hydrogen migration can be induced by exciting a molecule in many ways, as illustrated by mass or luminescence spectra resulting from electron impact ionization 10 , X-ray absorption 11 , and ionization following ion collisions 12 . A key tool for understanding hydrogen migration dynamics, developed over the course of the past few decades is ultrafast, strong-field laser induced ionization and dissociation of small hydrocarbons, including the simplest one, acetylene 1317 , and other polyatomic molecules, such as methanol 18 , ethylene glycol 19 , and acetonitrile 20 . Ultrashort VIS/NIR laser pulses with ~10 14 W/cm 2 intensities can singly or doubly ionize molecules in the gas phase, initiating hydrogen migration.…”
Section: Introductionmentioning
confidence: 99%
“…Such an experiment would be of particular interest for the vinylidene anion H2CCˉ, where it has been shown that excitation of non-totally symmetric modes of neutral H2CC drives isomerization to HCCH. 42 Overall, the range of applicability of IR cryo-SEVI remains to be determined, but any anion with a relatively isolated vibrational origin transition in its cryo-SEVI spectrum is a viable candidate.…”
Section: Resultsmentioning
confidence: 99%
“…Previous cryo-SEVI studies have uncovered myriad non-Born Oppenheimer behavior in small molecules that fail to be reproduced by FC simulations, most notably vibronic coupling. [134][135][136][137] The signatures of this phenomenon in cryo-SEVI are well established, arising due to borrowed electronic character from an excited state. 64,135,[137][138][139][140][141] Among these signatures are differing photoelectron angular distributions between transitions that are allowed only though vibronic coupling and those that are FC-allowed.…”
Section: Discussionmentioning
confidence: 99%